Five ways to get a grip on applying a program evaluation model in health professions education academies - Blanchard, Rebecca D; McDaniel, Katherine E; Engle, Deborah L (Canadian Medical Education Journal, 2024)
The proliferation of health professions educator academies across Canada and the United States illustrates the value they hold for faculty and institutions. Yet, establishing and evaluating the efficacy of them through program evaluation can be challenging. Moreover, academy leadership often lack the time, bandwidth skillset and personnel to undertake rigorous program evaluation efforts. We outline a step-by-step guide for getting a grip on evaluating health professions educator academies. Developing a plan for program evaluation in advance of any new academy initiative helps to ensure the academy calibrates and re-calibrates to accomplish outcomes and meet stakeholder expectations. It also provides a mechanism for tracking academy impact, which strengthens requests for funding, promotes sustainability and encourages continued buy-in and support from institutional stakeholders. For all of these reasons, we present the following recommendations: apply the relevant program evaluation framework(s); identify resources for program evaluation; prepare to tell your academy’s story; list desired program outcomes; establish a data collection plan; and obtain institutional review board approval.